2013
DOI: 10.1007/978-3-642-39077-7_12
|View full text |Cite
|
Sign up to set email alerts
|

How Much Is Too Much? Leveraging Ads Audience Estimation to Evaluate Public Profile Uniqueness

Abstract: Abstract. This paper addresses the important goal of quantifying the threat of linking external records to public Online Social Networks (OSN) user profiles, by providing a method to estimate the uniqueness of such profiles and by studying the amount of information carried by public profile attributes. Our first contribution is to leverage the Ads audience estimation platform of a major OSN to compute the information surprisal (IS) based uniqueness of public profiles, independently from the used profiles datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…For instance, analytics should produce reports only when the audience is composed of a minimum of k significantly different profiles similar to what is done in the Facebook Audience estimation platform [5]. On the other hand, addressing the identity spoofing vulnerability may be more challenging in practice.…”
Section: Potential Countermeasuresmentioning
confidence: 99%
“…For instance, analytics should produce reports only when the audience is composed of a minimum of k significantly different profiles similar to what is done in the Facebook Audience estimation platform [5]. On the other hand, addressing the identity spoofing vulnerability may be more challenging in practice.…”
Section: Potential Countermeasuresmentioning
confidence: 99%
“…-With the same dataset, we measured the amount of information contained in samples from the same gesture and from multiple gestures. 4 We found that 50 features in a single handwriting sample contribute 68.71% of information about users, which increases to 73.7% with multiple samples. We further identified that two or three different gestures combined together reveal more information about users.…”
Section: Introductionmentioning
confidence: 71%
“…To the best of our knowledge, this is the first study considering the potential of touch gestures to profile users. Our work complements research on other forms of tracking such as through web browsers, host devices, and online social profiles by fingerprinting browser features, device configurations, and user attributes [4,7,13,18,19,24,25,27,38]. -We develop an analytical framework that measures the amount of identifying information (in bits and relative mutual information) contained in touch gestures, represented as feature vectors, at different levels of granularity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To draw a baseline comparison, we also collected page like counts from a random set of 2000 Facebook users, extracted from an unbiased sample of Facebook user population. The original sample was crawled for another project[9], obtained by randomly sampling Facebook public directory which lists all the IDs of searchable profiles.…”
mentioning
confidence: 99%